Optimizing and Individualizing the Pharmacological Treatment of First-Episode Schizophrenic Patients: Study Protocol for a Multicenter Clinical Trial - Xiao, Jingmei; Huang, Jing; Long, Yujun; Wang, Xiaoyi; Wang, Ying; Yang, Ye; Hei, Gangrui; Sun, Mengxi; Zhao, Jin; Li, Li; Shao, Tiannan; Wang, Weiyan; et al. (Frontiers in Psychiatry, 2021)
Introduction: Affecting approximately 1% of the world population, schizophrenia is known as one of the costliest and most burdensome diseases worldwide. Antipsychotic medications are the main treatment for schizophrenia to control psychotic symptoms and efficiently prevent new crises. However, due to poor compliance, 74% of patients with schizophrenia discontinue medication within 1.5 years, which severely affects recovery and prognosis. Through research on intra and inter-individual variability based on a psychopathology- neuropsychology-neuroimage-genetics-physiology-biochemistry model, our main objective is to investigate an optimized and individualized antipsychotic-treatment regimen and precision treatment for first-episode schizophrenic patients. Methods and Analysis: The study is performed in 20 representive hospitals in China. Three sub-projects are included. In sub-project 1, 1,800 first-episode patients with schizophrenia are randomized into six different antipsychotic monotherapy groups (olanzapine, risperidone, aripiprazole, ziprasidone, amisulpride, and haloperidol) for an 8-week treatment. By identifying a set of potential biomarkers associated with antipsychotic treatment response, we intend tobuild a prediction model, which includes neuroimaging, epigenetics, environmental stress, neurocognition, eye movement, electrophysiology, and neurological biochemistry indexes. In sub-project 2, apart from verifying the prediction model establishedin sub-project 1 based on an independent cohort of 1,800 first-episode patients with schizophrenia, we recruit patients from a verification cohort who did not get effective response after an 8-week antipsychotic treatment into a randomized double-blind controlled trial with minocycline(200mg per day) and sulforaphane(3 tables per day) to explore add-on treatment for patients with schizophrenia. 240 participants are anticipated to be enrolled for each group. In sub-project 3, we tend to carry out one trial to construct a intervention strategy for metabolic syndrome induced by antipsychotic treatment, and another one to build a prevention strategy for patients at a high risk of metabolic syndrome, which combines metformin andlifestyle intervention. 200 participants are anticipated to be enrolled for each group. Ethics and Dissemination: The study protocol has been approved by the Medical Ethics committee of the Second Xiangya Hospital of Central South University (No. 2017027). Results will be disseminated in peer-reviewed journals and at international conferences. Trial registration: This trial has been registered on Clinicaltrials.gov (NCT03451734). The protocol version is V.1.0 (September 1, 2016).